Pengaruh Net Profit Margin dan Debt to Equity Ratio Terhadap Kebijakan Dividen Perusahaan BUMN di BEI: Studi Kasus Periode 2012-2021 - Shalsya, Nabilla; Situngkir, Tiar Lina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to discover, explain and conduct analysis regarding the impact of profitability (NPM) and leverage (DER) on the dividend policy of state-owned companies listed on the IDX for the 2012-2021 period. Quantitative methods with descriptive and verification approaches were used in the research. There were 20 state-owned companies that were the population in the research, then a purposive sampling technique was carried out so that 7 state-owned companies were selected that met the criteria. Panel data regression analysis is a data analysis method in research. In panel data regression testing, the results obtained were that the panel data regression model formed was a fixed effect model (FEM). Apart from that, a classical assumption test was also carried out. The research results show that profitability (NPM) and leverage (DER) simultaneously influence dividend policy in state-owned companies listed on the Indonesia Stock Exchange for the 2012-2021 period. Partially profitability (NPM) has no influence and is not significant on dividend policy, while leverage (DER) has an influence and is significant on dividend policy. The results of the analysis of the coefficient of determination show that the profitability (NPM) and leverage (DER) variables of 56.78% can predict dividend policy, while the remaining 43.22% is influenced by other factors not examined in the research.